Fintech Startups as Drivers of Effective, Sustainable, Social and Environmental Financial Inclusion - Hamou, Abdellah; Imansouren , Souhila; Hakmi , Nadjib Allah; Ouis , Latifa; Boulahbel , Samira; Chennouf , Hakim; Ouis , Nadjet (Journal of Ecohumanism, 2025)
This paper investigates the role of fintech start-ups in advancing financial inclusion and sustainable development across Africa. Fintech firms leverage digital technologies—artificial intelligence, blockchain, big data, and mobile platforms—to expand access to payments, credit, and wealth management. Using panel data for 20 African countries over 2010–2023, the analysis applies panel ARDL and fixed-effects models. Results show that mobile money transactions and internet penetration are the strongest determinants of financial inclusion, while fintech penetration and venture capital flows exert positive but heterogeneous effects. Findings highlight structural constraints, including regulatory fragmentation, digital divides, and geographic concentration of investment. Despite declining global funding, African fintech ecosystems remain resilient, positioning start-ups as catalysts for inclusive and sustainable growth.